Prenatal exercise for the prevention of gestational diabetes mellitus and hypertensive disorders of pregnancy: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Davenport, Margie H; Ruchat, Stephanie-May; Poitras, Veronica J; Jaramillo Garcia, Alejandra; Gray, Casey E; Barrowman, Nick; Skow, Rachel J; Meah, Victoria L; Riske, Laurel; Sobierajski, Frances; James, Marina; Kathol, Amariah J; et al.
Abstract : Objective: Gestational diabetes mellitus (GDM), gestational hypertension (GH) and pre-eclampsia (PE) are associated with short and long-term health issues for mother and child; prevention of these complications is critically important. This study aimed to perform a systematic review and meta-analysis of the relationships between prenatal exercise and GDM, GH and PE. Design: Systematic review with random effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were included (except case studies) if published in English, Spanish or French, and contained information on the Population (pregnant women without contraindication to exercise), Intervention (subjective or objective measures of frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [e.g., dietary; "exercise + co-intervention"]), Comparator (no exercise or different frequency, intensity, duration, volume and type of exercise) and Outcomes (GDM, GH, PE). Results: A total of 106 studies (n=273 182) were included. 'Moderate' to 'high'-quality evidence from randomised controlled trials revealed that exercise-only interventions, but not exercise+cointerventions, reduced odds of GDM (n=6934; OR 0.62, 95% CI 0.52 to 0.75), GH (n=5316; OR 0.61, 95% CI 0.43 to 0.85) and PE (n=3322; OR 0.59, 95% CI 0.37 to 0.9) compared with no exercise. To achieve at least a 25% reduction in the odds of developing GDM, PE and GH, pregnant women need to accumulate at least 600 MET-min/week of moderate-intensity exercise (eg, 140 min of brisk walking, water aerobics, stationary cycling or resistance training). Summary/conclusions: In conclusion, exercise-only interventions were effective at lowering the odds of developing GDM, GH and PE.